A novel approach for deoxycholic acid administration to treat submental fullness: A case report assessed by 3D stereophotogrammetry - Victor Rogerio; Viviane Rabelo; Pietra Roschel; Tatiane Sakemi; Marcelo Germani; Victor R.M. Munoz-Lora (Elsevier, 2024)
Background: While effective, DAc injections for submental fat (SMF) reduction carry risks, including vascular damage and skin necrosis when improperly administered. This study presents a novel approach to SMF reduction using blunt microcannulas for DAc injections, coupled with 3D stereophotogrammetry quantification (3D-SQ). Clinical presentation: A 47-year-old female with SMF underwent two DAc applications. 3D-SQ was performed before and after each treatment using a 3D-SQ system. The patient experienced a substantial total volume reduction of 14.81 mL in the submental area after two DAc applications. 3D-SQ analysis showed a gradual reduction in submental volume over time. Importantly, no serious adverse events were reported, with only minor pain and warmth at the treated site. The reduction of SMF through DAc injections involves adipocyte cell lysis, emphasizing the importance of proper injection technique to avoid adverse events. The use of blunt microcannulas offers a safer alternative, minimizing the risk of skin necrosis, ulceration, and intra-arterial injections. Additionally, cannulas reduce bruising due to their blunt design and fan technique, enhancing patient comfort and safety. Conclusion: This case report highlights the efficacy of a novel cannula approach for DAc SMF reduction, assessed by 3D-SQ. Blunt microcannulas may represent a safer option compared to hypodermic needles, reducing the likelihood of severe complications.